EQUESTRIAN ACCIDENTS – A REVIEW OF THE LITERATURE - Zuzanna Chwostek; Wiktoria Marzec; Hanna Maruchniak; Paulina Biedroń; Anna Skrzypek; Maciej Hutkowski; Mikołaj Zbrożek; Bartłomiej Kosiarski; Patrycja Markowicz; Krzysztof Biłyk (International Journal of Innovative Technologies in Social Science, 2026)
Introduction and objective: Horse riding is a sport that has become an increasingly popular form of physical activity in recent years, both at amateur and professional levels. The aim of the review was an epidemiological analysis of horse-riding-related injuries, along with the identification of their most common risk factors and mechanisms.Review methods: A systematic literature search was conducted using PubMed and Google Scholar. The search employed terms such as 'horse riding,' 'injuries,' 'spine,' 'vertebral,' 'horse-related,'and 'back injuries.' Articles published between 2014 and 2025 were included in the search. Highly cited papers published more than a decade ago are also includedBrief description of the state of knowledge: Young women constitute the largest group among individuals sustaining horse-related injuries. This observation reflects their greater participation in equestrian activities rather than sex-related differences in injury susceptibility. The predominant mechanism of injury is a fall from the horse. Middle-aged men most commonly sustain injuries related to horse handling activities, typically resulting from mechanisms such as kicking, biting, or being stepped on by the horse. Injuries most frequently involve the extremities, the spine—predominantly the lumbar region—and the thoracic cage. Head injuries are associated with higher mortality rates and an increased risk of permanent health impairment. Available data regarding the effectiveness of protective equipment, including helmets and body protectors, suggest a reduction in the severity of sustained injuries.Summary: Horse riding is a sport with an increased risk of injury. Multidirectional actions are needed to improve safety through appropriate and continuous training of riders, correct and efficient equipment and the use of certified protective measures.